2011
DOI: 10.1007/s12350-011-9413-9
|View full text |Cite
|
Sign up to set email alerts
|

Main pulmonary artery diameter from attenuation correction CT scans in cardiac SPECT accurately predicts pulmonary hypertension

Abstract: MPA diameter from low-dose unenhanced multi-slice CT reliably predicts PHT, providing an important added clinical value from AC for SPECT MPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In all included studies, most studies used RHC as the gold standard to diagnose PH, which is widely considered as an acceptable basis for PH diagnosis, 3 studies only used echocardiography as diagnostic reference. 25 , 37 , 38 Of the 20 publications, 15 had QUADAS scores ≥9, suggesting the reliable of our results. Tables 1 and 2 summarized the clinical characteristics of the studies, patient distribution in each study as well as the QUADAS scores for each publication.…”
Section: Resultssupporting
confidence: 67%
“…In all included studies, most studies used RHC as the gold standard to diagnose PH, which is widely considered as an acceptable basis for PH diagnosis, 3 studies only used echocardiography as diagnostic reference. 25 , 37 , 38 Of the 20 publications, 15 had QUADAS scores ≥9, suggesting the reliable of our results. Tables 1 and 2 summarized the clinical characteristics of the studies, patient distribution in each study as well as the QUADAS scores for each publication.…”
Section: Resultssupporting
confidence: 67%
“…A wide range of cut-off values for identifying RHC-confirmed pulmonary hypertension have been proposed for MPAD (from 25 to 38 mm) and PA:Ao (from 0.84 to 1.4) [4,6,7,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. We elected to use the cut-offs proposed in the European Society of Cardiology/European Respiratory Society pulmonary hypertension guideline for our main analyses [13,14], but also ran analyses using a range of values, and found that alternative cut-off values performed better.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study population, the cut-off selected for the PA diameter (25-33.3 mm), and the gold standard used, the reported sensitivity can range between 47%-100% and the specificity between 41%-100% [10,12,13,[16][17][18][20][21][22]28]. As anticipated, there is considerable overlap in the cut-off value and some overlap with what has been reported in the population without PH (Table 1).…”
Section: Diagnostic Utility Of Pa Sizementioning
confidence: 76%